International Students’ Experience of Studying at Indonesian Universities: A Systematic Review - Widiasih, Restuning; Hermayanti, Yanti; Ermiati, (Journal of International Students, 2020)
This article reports a systematic review of articles published between 2009 and 2019 focusing specifically on the experiences of international students studying at Indonesian universities. We used such international databases as PubMed and CINAHL, and a national database, SINTA. The articles abstracted in such databases were screened out using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. The analysis of the six selected articles found that international students studying in Indonesia encountered such challenges as cultural adaptations, language problems, and differences in the educational system. The international students also experienced health care systems different from those of their home country. This empirical evidence suggests that prospective international students who plan to study in Indonesia should be well-informed of both academic and non-academic matters that they may encounter or they may have to anticipate.